PENGEMBANGAN QUANTUM LEARNING MELALUI UMMI BERBASIS SOFTWARE CAMTASIA STUDIO MATERI STRUKTUR ALJABAR DALAM PENINGKATAN NILAI PENDIDIKAN KARAKTER BANGSA - Aziz, Abdul; Saputra, Meidi (Jurnal Karya Pendidikan Matematika, 2018)
Learning Multimedia is a graphical software made through Camtasia Studio that has advantages in knowing the position (position) of an image from an algebraic equation or inequality, quadratic function, etc. The application of multimedia learning will be able to improve spatial quotient, which is spatial quotient is one of multiple intelligences that focuses more on the ability to analyze images or space and the subject matter Algebraic Structure is one of the material that prioritizes analyzing images or graphics. Based on the description above, in this study will use the Quantum Learning method based on Camtasia StudioThe purpose of this study is to produce learning devices as an implementation of the Camtasia Studio-based Quantum Learning method through research and development (Research and Development). The expected output of this study is a draft textbook Introduction to Algebraic Structure and Quantum Learning methods with Camtasia Studio.